Análise fonética de um sistema caseiro de sinais: a complexidade das configurações de mãos - Silva, Hidelbrando Rodrigues da (Brasil, 2024)
This is set in the field of linguistic studies of emerging sign languages, of the homesign systems type, its main objective is to analyze the linguistic aspects of the homesign systems of deaf students enrolled in the education networks of Manaus, specifically, sustaining whether to identify the phonemes of the hand configuration parameter of the homesign system of a deaf student enrolled in the education systems of Manaus; and, classify the complexity of the hand-shape phonemes of the homesign system of a deaf student enrolled in the education systems of Manaus. To meet this proposition, research was based on a qualitative, quantitive and field-type approach. Sources of information were collected from bibliographic and field research. To this end, a narrative review of the literature and semi-structured interview techniques were used, in addition to a spontaneous demonstration of a semantic album. It is theoretically supported mainly by: Brentari and Eccarius (2010), Brentari et al. (2012) and Stoianov et. al. (2022). The results indicate 38 signs/classifiers and 22 phonemes of the hand configuration parameter. As for the complexity of articulation, the use of handling signs/classifiers with a low level of complexity was observed, proving the influence of hearing users and their spontaneous gestures on the lexical composition of this homesign system. When the complexity of fingers, object signs/classifiers present greater complexity than handling signs/classifiers, proving the hypothesis that homesign systems have the same linguistic status as established languages